Micromechanics of Amorphous Metal/Polymer Hybrid Structures with 3D Cellular Architectures: Size Effects, Buckling Behavior, and Energy Absorption Capability. Issue 8 (14th December 2016) - Mieszala, Maxime; Hasegawa, Madoka; Guillonneau, Gaylord; Bauer, Jens; Raghavan, Rejin; Frantz, Cédric; Kraft, Oliver; Mischler, Stefano; Michler, Johann; Philippe, Laetitia
Abstract : By designing advantageous cellular geometries and combining the material size effects at the nanometer scale, lightweight hybrid microarchitectured materials with tailored structural properties are achieved. Prior studies reported the mechanical properties of high strength cellular ceramic composites, obtained by atomic layer deposition. However, few studies have examined the properties of similar structures with metal coatings. To determine the mechanical performance of polymer cellular structures reinforced with a metal coating, 3D laser lithography and electroless deposition of an amorphous layer of nickel‐boron (NiB) is used for the first time to produce metal/polymer hybrid structures. In this work, the mechanical response of microarchitectured structures is investigated with an emphasis on the effects of the architecture and the amorphous NiB thickness on their deformation mechanisms and energy absorption capability. Microcompression experiments show an enhancement of the mechanical properties with the NiB thickness, suggesting that the deformation mechanism and the buckling behavior are controlled by the brittle‐to‐ductile transition in the NiB layer. In addition, the energy absorption properties demonstrate the possibility of tuning the energy absorption efficiency with adequate designs. These findings suggest that microarchitectured metal/polymer hybrid structures are effective in producing materials with unique property combinations. Abstract : Metal–polymer composite microarchitectures with controllable plastic deformation and energy absorption are synthesized by plating an amorphous NiB layer onto a 3D polymeric template. Under uniaxial compression testing, the microarchitectures buckle or fail catastrophically depending on the NiB layer thickness. This behavior results from the ductile‐to‐brittle transition observed at this length scale in the amorphous NiB layer.